(3GdbQHIs - (3eMeO Hf Ydj Hf eMeO Hf YQHj , CHh HcQ GdMGJej GdWGFj GdCfOdSj, GdeYQha HeMjj GdOjf GHf YQHj,J (B638 (3g` s
(3ChdgG (B:s
(3GdMeO ddg eNUU ef TGA ef YHGOg HNUGFU Ydhe GdGdgGe aUGQJ GdcdeI YQHjI YQHG HYOeG cGfJ CYLejI s
(3BNQgG (B:s
(3Edi Cf hbaJ dCHi YHO GdQMef GdSdei ai HYV cJHg Ydjg fUkG hSeGg ebGe GdbQHI Je GdcJGH s
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B281s
(3eUOQ GbJfGA GdCUd (B:s
(3eLdS ThQGi (B(294) s
Keywords: (3GdJUha hGdBOGH GdTQYjIs